Bottleneck adjacent matching 1 (bam1) heuristic for re-entrant flow shop with dominant machine - Ahmad Bareduan, Salleh (2008)

(untitled)
This paper presents a scheduling heuristic to minimize the makespan of a re-entrant flow shop using bottleneck analysis. The heuristic is specifically intended for the cyber manufacturing centre (CMC) which is an Internet-based collaborative design and manufacturing between the Universiti Tun Hussein Onn Malaysia and the small and medium enterprises. The CMC processes scheduling resembles a four machine permutation reentrant flow shop with the process routing of M1,M2,M3,M4,M3,M4 in which the combination of the last three processes of M4,M3,M4 has high tendency of exhibiting dominant machine characteristic. It was shown that using bottleneckbased analysis, an effective constructive heuristic can be developed to solve for near-optimal scheduling sequence. At strong machine dominance level and large job numbers, this heuristic shows slightly better makespan performance compared to the NEH. However, for smaller job numbers, NEH is superior.